Tinjauan Yuridis Perlindungan Hukum Korban Tindak Pidana Pemerkosaan Yang Menderita Gangguan Kejiwaan Berdasarkan Undang-Undang Nomor 31 Tahun 2014 Tentang Perubahan Undang- Undang Nomor 13 Tahun 2006 Tentang Perlindungan Saksi dan Korban - Karina, Gerith; Firdaus, Emilda; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Errors of Practice (malpractice) occur or caused a malfunction that can be less cautious, less careful, and less seriousness in the anamnesis, examination, diagnosis, therapy/treatment and follow-up, on the other side because it is less skilled and lack of knowledge from the healthcare personnel concerned. The study titled "Criminal Liability for health workers against malpractice and Negligence in Khitan Action (circumcision)", has a formulation of the issue of how health criminal liability for malpractice and Negligence in the action of circumcision (circumcision), and how should the ideal arrangement against health workers who perform malpractice and negligence in the actions of circumcision (circumcision).The purpose of writing this thesis is: First, to know the criminal liability of health workers against malpractice and negligence in the act of circumcision (circumcision). Secondly, to know the ideal setting of health personnel who perform malpractice and negligence in the action of circumcision (circumcision).This type of research is normative legal research or can also be called by doctrinal law research. From the results of the research problem there are two points that are concluded, firstly, in case the nurse proved and fulfill the element of doing malpractice or omission in the action of the Kkhitan (circumcision) to the patient then the nurse can be asked Criminal liability. Secondly, in the Indonesian legal system speaking of regulations that ideally is a rule that should be or is not done by health workers (caregivers) in terms of the provision of services of circumcision action (circumcision). For the case of circumcision action (circumcision) should be made renewal or policy which contains the extent of the rights and obligations to be done by the nurse.Key words: Negligence – Circumcision – Regulation - Ideally